Preparation and qualification of soluble amyloid beta oligomers for use in bioanalytic assays supporting Alzheimer's disease therapeutics. (20th December 2022) - Cline, Erika N.; Vanderstichele, Hugo Marcel; Johnson, Derrick; Abdeen, Sanofar Jainul; McDermott, Paul; Cruse, James; Viola, Kirsten L.; Dean, Robert A; Jerecic, Jasna
Abstract: Background: Soluble amyloid beta oligomers (sAβOs) accumulate early in Alzheimer's disease (AD) and trigger AD‐related neuropathologies and impairments in memory. sAβO structures contributing to the neurotoxic effects remain ill‐defined due to their low concentration, instability, and heterogeneity, impeding the effective design and use of sAβO reference standards in bioanalytic assays for use in clinical trials. At present, no assays for sAβOs are available with proven robustness and clinical performance, due to absence of well‐characterized critical raw materials (antibodies, reference materials for preparation of sAβO calibrators) and quality control specimens. Method: We have used amyloid‐derived diffusible ligands (ADDLs), a synthetic model preparation commonly used in the literature (Stine et al. 2003), as a sAβO standard integrated into different assays designs developed on the Mesoscale Discovery (MSD) technology. As proof‐of‐concept, we have utilized these ADDL assays to study the specificity and selectivity of antibodies targeted against sAβOs. Result: Optimization of ADDL coating, stabilization of coated materials, and long‐term plate stability indicated that ADDL‐coated plates provided a suitable platform to assess the performance of sAβO‐targeting antibodies. Prior to coating, ADDL preparations were tested for reproducible SDS‐stable size distribution and immunoreactivity using SDS‐PAGE with silver stain and Western immunoblotting. The native size distribution (SEC) and globular conformation (AFM) of ADDLs and their ability to bind neuronal synapses in culture (ICC) and subsequently elicit AD‐related pathologies has been well reported in the literature. ADDLs were coated onto 96‐well MSD plates and the ADDL‐coated plates were stored at 4 °C for long‐term use; plate stability was confirmed up to one year. Biotinylated and non‐biotinylated sAβO‐targeting antibodies with variable selectivity towards monomeric or oligomeric Aβ species were used for comparative binding analysis. Additional sAβO preparations, including low concentration ADDL preparations and commercially available sAβOs were used to further understand the selectivity and specificity of the panel of sAβO‐targeting antibodies. Conclusion: Qualified sAβO preparations (ADDLs) can be used as tools for coating plates to determine specificity and selectivity of sAβO‐targeting antibodies. Other expected uses are: (i) calibrator in immunoassays; or (ii) to screen for the presence of sAβO auto‐antibodies in biological fluids.